Coagulation Profile Is Not a Predictor of Acute Cerebrovascular Events in Pediatric Extracorporeal Membrane Oxygenation Patients. Issue 6 (November 2017) - Anton-Martin, Pilar; Journeycake, Janna; Modem, Vinai; Golla, Sailaja; Raman, Lakshmi; Tweed, Jefferson; Darnell-Bowens, Cindy
Abstract : We performed a retrospective matched case–control study evaluating whether the traditional coagulation profile predicts cerebrovascular events in children on extracorporeal membrane oxygenation (ECMO) in a 71 bed intensive care unit at a tertiary children's hospital. Between 2009 and 2014, 241 neonates and children were initiated on ECMO. The cumulative 5 year incidence of intracranial hemorrhage and infarct was 9.2% and 7.9%, respectively. Thirty-six cases were individually matched 1:1 with control subjects based on age, primary diagnosis, ECMO type, cannulation site, and the presence of pre-ECMO coagulopathy. In-hospital mortality was higher among the cases compared with control subjects (78 vs. 22%, p < 0.01). The median laboratory values that assisted with heparin anticoagulation monitoring (activated clotting time, partial thromboplastin time, and antifactor Xa) and the laboratory data that assisted with blood product administration (platelet count, prothrombin time, fibrinogen, and d-dimer) during the 24 and 72 hour periods before the cerebrovascular event did not show any significant difference between the hemorrhage group and their controls or between the infarct group and their controls. The traditional coagulation profile did not predict acute cerebrovascular events in our cohort. Other markers of neurologic injury on ECMO are yet to be elucidated. Prospective studies to determine better predictors of cerebrovascular complications in pediatric ECMO patients are required. Abstract : Supplemental Digital Content is available in the text.